Metal ions leachables from fake orthodontic braces incubated in simulated body fluid - Riyam Haleem; Noor Ayuni Ahmad Shafiai; Siti Noor Fazliah Mohd Noor (BMC, 2021)
Abstract Background The demand for fake braces usage in Southeast Asia are increasing but lack of certification and information on fake braces as medical devices from regulated bodies raised a concern towards its safety. The aim of this study was to determine the types of metal ion leachable from removable fake braces based on heavy metal ions present in metallic materials, immersed in simulated body fluid (SBF) and analysed using inductively coupled plasma atomic emission spectroscopy. Methods Three sets of fake braces and one control were dissembled to only their brackets and archwires and immersed separately in SBF. They were placed in an incubator shaker at a temperature of 37 °C at 50 rpm. A 3.0 ml measurement of SBF was taken out from the sample containers at days 7, 14 and 28 and kept at − 20 °C for further analysis. Data were analysed using SPSS version 26.0 (IBM, Armonk, USA) (P < 0.05). Descriptive and one-way ANOVA analyses with Bonferroni post hoc tests were used to assess the significant differences between the metal ions released in SBF from the control samples and fake braces. Results All 23 elements under investigation except Si ions were detected from the control samples and fake braces. There were significant increased K ions and reduced levels of Mg ions from the fake archwires and brackets. Most ions released were less than 10 mg/L (Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Mo, Cd, Pb, Al) or 1 mg/L (Li, Ba) into the SBF medium. Conclusion There were significant release of Ca and K ions from the fake samples. Elements such as Li, Ba, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Mo, Cd and Sb had increased in concentration at day 7 and the concentration plateaued until day 28.